2008
DOI: 10.1007/s00595-008-3785-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine attenuates intestinal ischemia/reperfusion injury in rats

Abstract: These results provide further evidence of the anti-inflammatory and anti-apoptotic activities of oxymatrine, which may become a potent drug for protecting the intestines against I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…It is proven to protect ischemic and reperfusion injury in liver, intestine and heart via anti-inflammation and antiapoptosis [12,21,22]. Recently, several studies have confirmed that OMT protects the brain from ischemic injury by an inhibition of the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is proven to protect ischemic and reperfusion injury in liver, intestine and heart via anti-inflammation and antiapoptosis [12,21,22]. Recently, several studies have confirmed that OMT protects the brain from ischemic injury by an inhibition of the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…OMT has been proved to have a variety of biological effects in treatment of viral hepatitis 8 , bronchial asthma 9 and ischemic injuries [10][11][12][13][14][15][16]22 , and plays a role in scavenging activity against reactive oxygen species 18 . In view of these considerations, we tested the therapeutic potentials of OMT on renal I/R injury rat model.…”
Section: Discussionmentioning
confidence: 99%
“…, liver 12 , intestinal 13 and brain [14][15][16] ischemia/reperfusion injury in animal models. OMT also have a protective role in adriamycin-induced chronic renal fibrosis 17 .…”
mentioning
confidence: 99%
“…(Kushen) that has been approved by the State Food and Drug Administration of China for treating hepatitis B (7,8). Cumulative evidence has suggested that OM possesses multiple biological and pharmacological properties, such as anti-inflammatory (9)(10)(11), antitumor (12,13), anti-apoptotic (14), antifibrotic (15), antioxidant (16), and antiarrhythmic activities (17). Chen et al (18) demonstrated that…”
Section: Introductionmentioning
confidence: 99%